Developing and testing of a Collector-Cum-Storage Type Solar Water Heater for domestic use - Bijukumar K (Department of Farm Power Machinery and Energy, Kelappaji College of Agricultural Engineering and Technology, 2000)
The present study was undertaken to desi~n and develop a collector-cum-storage type solar water heater of 30 litre capacity to supply hot water for domestic use. Five solar water heaters with different absorber plate positions were constructed. The storage tanks with dimensions of 67 xIl7 x 10 cm were made by using fibre glass, and the top of these storage tanks were covered using single plain glass plates of 71 x 51 x 0.4 cm size. The position of the absorber plate was varied by changing the width of the spacers (4 nos. at an angle of 400 with the side aluminium sheet), which connects bottom aluminium plate and top absorber plate. The absorber plate was of 65 x 45 cm size. The top face of the absorber plate was painted black to absorb maximum solar. radiation. The absorber plate positions were lcm, 3cm, 5cm, 7cm and 9cm from the top glass cover plate and were designated as SWHl 0, SWH30, SWH5.0, SWH7.0 and SWH9.0 respectively. The absorber plate position was optimized by testing the solar water heaters under two different test conditions. Solar water heater II (SWH3.0) outperforms other solar water heaters under the two test conditions. Maximum outlet temperature of 64°C af 3pm and maximum efficiency of 55.72% also at 3pm were observed in solar water heater 11. So it is optimized that the position of the absorber plate should be at 3cm from . the top glass plate. The solar warer heater can easily be handled by a single person since the weight is only 9.5kg. The operating cost per unit of thermal energy obtained withthe solar water heater was found to be 25 paise per kWh.